Murals of Budapest in the age of creative cities - Murányi, Kata (2016)
The concepts of creative city and creative economy along with the cultural city development were born in the 1970s, when traditionally industrial centers had started to decline. From the 1990s on there has been a constant discussion of Western European and North American cities’ post-fordist culture and technology based transformation. Since the appearance of Richard Florida’s book The Rise of the Creative Class, the concept of creative city has become a fashionable and often used terminology, and in this sense there is wide acceptance of a social and economic arrangement that is based on the so-called creative class, which tends to settle down in cities open to creativity. Florida’s theory was taken over by Hungarian professional and academic circles without much criticism, and creative city is still a beloved expression and approach while discussing Budapest’s strategic vision. In this writing I analyze why street art, as a thoughtful expression of creativity, artist’s freedom and reflection of urban life, is still not sufficiently emphasized and remains in the periphery of the post-socialist Hungarian capital.